Paul M. Robinett papers - Robinett, Paul M. (Paul McDonald), 1893-1975.; Robinett, Paul M. (Paul McDonald), 1893-1975.
Correspondence, diary, speeches, writings, military orders and training material, printed matter, and other papers relating to Robinett's career as combat commander, commandant of the Armored Force School (U.S.), Fort Knox, Ky., and chief, Special Studies Section, Office of the Chief of Military History. Reflects his interest in military history, particularly the history of the cavalry. Subjects include military education, functions of armored divisons in World War II especially the Tunisian campaign in North Africa, and political and military strategy during the Cold War. Includes a draft of Robinett's book (1958) and summaries of directives to and from Adna Romanza Chaffee concerning armored warfare, 1938-1943. Correspondents include William S. Biddle, Omar Bradley, Malin Craig, Lloyd R. Fredendall, St. Clair Streett, Arthur W. Vanaman, Orlando Ward, and Isaac Davis White.
Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Biddle, William S. -- 1900-1981 -- Correspondence; Bradley, Omar Nelson, -- 1893-1981 -- Correspondence; Chaffee, Adna Romanza, -- 1842-1914.; Craig, Malin, -- 1875-1945 -- Correspondence; Fredendall, Lloyd R. -- 1883-1963 -- Correspondence; Streett, St. Clair, -- 1893-1970 -- Correspondence; Vanaman, Arthur W. -- 1892-1987 -- Correspondence; Ward, Orlando, -- 1891-1972 -- Correspondence; White, Isaac D. -- 1901-1990 -- Correspondence; United States. -- Army -- History; United States. -- Army. -- Cavalry -- History; Armored Force School (U.S.); Cavalry -- History; Cold War; Military education; Military history; Military policy; World politics -- 1945-1989.; World War, 1939-1945 -- Africa, North; World War, 1939-1945 -- Campaigns -- Tunisia; Fort Knox (Ky.) -- History; United States -- Armed Forces -- Armored troops; United States -- History, Military; United States -- Military policy -- 20th century; Army officers